Impact on wellness and adaptation by stakeholders in challenging time: A sequential explanatory mix-method study - Shuh Shing Lee; Shefaly Shorey; Tang Ching Lau; Dujeepa D. Samarasekera (The Asia Pacific Scholar)
Introduction: Numerous studies have been conducted on COVID-19, with the majority focusing on interventions involving students and teachers. However, limited research has delved into the pandemic's impact on the wellness of various stakeholders and how they have adapted to the challenges it presented. This study aims to fill this gap by exploring these neglected areas. Methods: This study employs a sequential mixed-method approach to study these areas. The quantitative data collection was carried out using a combination of validated surveys (ranging between 63-88 items) for students, faculty and administrators. Subsequently, qualitative data collection was gathered via semi-structured interview using a convenient sampling method. Results: Seventeen faculty, 18 administrators and 369 students responded to the survey. The quantitative data indicated faculty (teachers) exhibited the lowest stress levels and the highest resilience during the pandemic. In comparison, administrators and students experienced moderate levels of stress, with students scoring slightly higher on the stress level. The themes that emerged from the qualitative data were personal endurance, emotional reaction, cognitive-behavioural reaction and social support. Conclusion: Our study highlighted that, apart from personal endurance, the tension arises from emotional and cognitive-behavioural responses of students, teachers, and administrators can be mitigated based on the presence or absence of support mechanisms.